2023
DOI: 10.4236/ojrad.2023.134023
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Ultrasound Correlation in Women Presenting with Breast Lumps in Yaoundé, Cameroon

Yann Chris Mannel Eng,
Ambroise Merci Seme Engoumou,
Armel Philippe Awana
et al.

Abstract: Context: Breast cancer is very deadly among women with higher rates in the developing world. Imaging tools such as ultrasound, can be used to differentiate between the types of breast lumps. This study aimed to determine the value of ultrasound as a first-line examination in the diagnosis of breast masses. Methods: This was a retrospective cross-sectional study of women presenting with breast lumps from November 2022 to June 2023 at the Yaounde General Hospital, which lasted seven months, from November 2022 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Utilized as an adjunctive screening modality, breast ultrasonography has demonstrated notable advantages in identifying extra malignancies that may escape detection with mammography alone. Recent research has indicated substantial enhancements in overall sensitivity, hence decreasing the probability of undiscovered malignancies in women with thick breasts [ 17 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. While one study suggests that the sensitivity and specificity of ultrasound, compared to the histopathological results, are at 85.8%, and 73.3%, respectively [ 41 ], another study compared the accuracy of ultrasound and mammography in terms of lesion’s dimensions.…”
Section: Advantages Of Breast Ultrasound In Breast Cancer Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilized as an adjunctive screening modality, breast ultrasonography has demonstrated notable advantages in identifying extra malignancies that may escape detection with mammography alone. Recent research has indicated substantial enhancements in overall sensitivity, hence decreasing the probability of undiscovered malignancies in women with thick breasts [ 17 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. While one study suggests that the sensitivity and specificity of ultrasound, compared to the histopathological results, are at 85.8%, and 73.3%, respectively [ 41 ], another study compared the accuracy of ultrasound and mammography in terms of lesion’s dimensions.…”
Section: Advantages Of Breast Ultrasound In Breast Cancer Screeningmentioning
confidence: 99%
“…Recent research has indicated substantial enhancements in overall sensitivity, hence decreasing the probability of undiscovered malignancies in women with thick breasts [ 17 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. While one study suggests that the sensitivity and specificity of ultrasound, compared to the histopathological results, are at 85.8%, and 73.3%, respectively [ 41 ], another study compared the accuracy of ultrasound and mammography in terms of lesion’s dimensions. Thus, it was demonstrated that the specificity is higher for both of the methods (78.7% for mammography and 92.9% for ultrasound), when the lesion is between 1.1 and 2 cm, compared to the specificities for lesions smaller than 1 cm (65.2% for mammography and 85.1% for ultrasound [ 42 ].…”
Section: Advantages Of Breast Ultrasound In Breast Cancer Screeningmentioning
confidence: 99%